Brain abscess developing at the site of preceding stroke - Report of three cases: Review of literature - Kaplan, M; Ozveren, MF; Erol, FS; Kaplan, S; Bilge, T (Lippincott Williams & Wilkins, 2005)
Abscess formation after a stroke is a rare event. The 3 cases treated at our clinic are presented in combination with an evaluation of other previously reported cases so as to establish their common characteristics. One of the cases had the characteristics of nonseptic ischemic stroke, whereas the other 2 had characteristics of hemorrhagic stroke. The patients presented to our clinic in the early poststroke period with complaints of headache of increasing intensity, nausea, and vomiting. All 3 cases had other infection findings, and there were no new neurologic deficits other than those related to the stroke. The diagnoses of abscess formation at the same location as the stroke were established through cranial computed tomography or cranial magnetic resonance imaging. The diagnoses were also confirmed by microscopic evaluation. After drainage of the abscess, treatment involved 8 weeks of antibiotic treatment based on antibiogram results. Stroke facilitates the formation of an abscess at the same location. The early period of the first 3 months after a stroke is when there is the highest risk for this complication. The most prevalent source of infection is bronchopulmonary. An abscess usually presents with deterioration of neurologic condition, increased intracranial pressure, and findings of infection. Because it is located at the same location as the stroke, however, it may not create additional new neurologic deficits. The stroke experienced previously does not affect the efficiency and treatment time of the antibiotics used after drainage of the abscess.
Keywords: brain abscess; complication; stroke